Epidermal carbonic anhydrase activity and exoskeletal metal content during the molting cycle of the blue crab, Callinectes sapidus. Issue 3 (2nd March 2016) - Calhoun, Stacy; Zou, Enmin
ABSTRACT: During the crustacean molting cycle, the exoskeleton is first mineralized in postmolt and intermolt and then presumably demineralized in premolt in order for epidermal retraction to occur. The mineralization process calls for divalent metal ions, such as Ca 2+ and Mg 2+, and bicarbonate ions whereas protons are necessary for dissolution of carbonate salts. Carbonic anhydrase (CA) has been suggested to be involved in exoskeletal mineralization by providing bicarbonate ions through catalyzing the reaction of carbon dioxide hydration. However, results of earlier studies on the role of epidermal CA in metal incorporation in crustacean exoskeleton are not consistent. This study was aimed to provide further evidence to support the notion that epidermal CA is involved in exoskeletal mineralization using the blue crab, Callinectes sapidus (Rathbun 1896), as the model crustacean. Significant increases first in calcium and magnesium then in manganese post‐ecdysis indicate significant metal deposition during postmolt and intermolt. Significant positive correlation between calcium or magnesium content and epidermal CA activity in postmolt and intermolt constitutes evidence that CA is involved in the mineralization of the crustacean exoskeleton. Additionally, we proposed a hypothetical model to describe the role of epidermal CA in both mineralization and demineralization of the exoskeleton based on the results of epidermal CA activity and exoskeletal metal content during the molting cycle. Furthermore, we found that the pattern of epidermal CA activity during the molting cycle of C. sapidus is similar to that of ecdysteroids reported for the same species, suggesting that epidermal CA activity may be under control of the molting hormones. J. Exp. Zool. 9999A:XX–XX, 2016. © 2016 Wiley Periodicals, Inc.